Antibodies to alcohol altered liver cell determinants in patients with alcoholic liver disease. Issue 3 (March 1984) - Neuberger, J; Crossley, I R; Saunders, J B; Davis, M; Portmann, B; Eddleston, A L; Williams, R
Abstract : Circulating antibodies reacting specifically with hepatocytes isolated from ethanol pretreated rabbits have been demonstrated by two techniques - induced cytotoxicity and immunofluorescence. In the cytotoxicity assay antibodies were found in seven of 19 (39%) of patients with alcoholic fatty liver (with or without fibrosis), six of 13 (46%) of those with alcoholic hepatitis, 15 of 36 (43%) of those with cirrhosis, and seven of 14 patients (50%) of those with hepatitis and cirrhosis. In the immunofluorescence studies, nine of 15 sera induced a granular pattern of fluorescence on the ethanol pretreated hepatocytes; two sera which induced significant cytotoxicity did not induce immunofluorescence. No ethanol related antibodies were found in normal individuals or in patients with other types of acute or chronic liver disease. These results show that antibodies directed against ethanol altered liver cell determinants are present in the serum of 43% of patients with alcoholic liver disease, and suggest a mechanism whereby chronic alcohol consumption may, by inducing antigenic changes in hepatocyte membranes, trigger a cell damaging immune reaction.